(3GdJQLeGf GdoeYQH Yf Ohd GdeTQb hGdeZQHs - (3CHhGdbGSe Hf CMeOHf Ydj Hf EHQGgje GdRjGfjs
(3ChdgG (B:s
(3hHYO Efj deG cfJ CjGe GdNWI GdNSjSI eYOhOkG ai OjhGf GdcJGH CJbdH ai CbWGQ GdeZQH TQbkG hZQHkG , hCJhLg ai GdSaGQI Hjf GdOhd SdekG hMQHkG s
(3BNQgG (B:s
(3hgPG LegQI GdYQH cdgG YOfGfgG hbMWGfjgG hESQGFjdgG hQhegG efHg Ydjge HMhdg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B172s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B879 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B106 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B((3O (B658) s
Keywords: (3GdJGQjNs